Pengaruh Budaya Patriarki terhadap Pengambilan Keputusan dalam Ber KB pada Pasangan Usia Reproduksi di Desa Curug Kecamatan Klari Kabupaten Karawang - Rahmadyanti Rahmadyanti; Fatin Nuha Yamin (Universitas Malahayati Lampung, 2024)
ABSTRACT Family planning participants are couples of childbearing age (PUS) who are currently using one of the contraceptives without pregnancy. PUS family planning participants consist of modern family planning participants (using contraceptive devices/drugs/methods in the form of female sterile (MOW), male sterile (MOP), IUD/AKDR). Implants/implants, injections, pills, condoms and the Lactational Amenorrhea Method (MAL) and traditional family planning participants (using contraceptive devices/drugs/methods in the form of periodic abstinence, interrupted intercourse, and other traditional contraceptive devices/medicines/methods). Patriarchal culture makes men dominate every decision in the household, including the issue of determining the number of children. PUS can get contraceptive services at places that serve family planning programs. To determine the influence of patriarchal culture on reproductive age couples' decision making regarding family planning in Curug Village, Klari District, Karawang Regency in 2023. Using qualitative. The research population was all couples of childbearing age in the Telukjambe area, specifically in Curug Village, Klari District, as many as 150 respondents. The sampling technique usespurposive sampling with a sample size of 60 respondents.Analis bivariate using testChi-square. Based on the chi square test with CI = 95%, the p value .001 (P 0.05) is obtained, which means there is a significant relationship between patriarchal culture and decision making in family planning among couples of productive age in Curug Village, Klari District, Karawang Regency in 2023. The conclusion is that there is a significant relationship between patriarchal culture and decision-making in family planning for couples of productive age in Curug Village, Klari District, Karawang Regency in 2023. It is recommended in this research for educational institutions, for research sites, for respondents and for further researchers. Keywords: Patriarchal Culture, Birth Control, Reproductive Age ABSTRAK Peserta KB adalah Pasangan Usia Subur (PUS) yang saat ini sedang menggunakan salah satu alat kontrasepsi tanpa diselingi kehamilan. PUS peserta KB terdiri dari peserta KB modern (mengunakan alat/obat/cara KB berupa steril wanita (MOW), steril pria (MOP), IUD/AKDR). Implan/susuk, suntik, pil, kondom dan Metode Amenore Laktasi (MAL) dan peserta KB tradisional (menggunakan alat/obat/cara KB berupa pantang berkala, senggama terputus, dan alat/obat/cara KB tradisional lainnya). Budaya patriarki membuat laki-laki lebih mendominasi dalam setiap keputusan di dalam rumah tangga termasuk permasalahan dalam menentukan jumlah anak. PUS bisa mendapatkan pelayanan kontrasepsi di tempat-tempat yang melayani program KB. Untuk mengetahui Pengaruh Budaya Patriarki terhadap pengambilan keputusan pasangan usia reproduksi dalam ber KB di Desa Curug Kecamatan Klari Kabupaten Karawang Tahun 2023. Menggunakan kualitatif. Populasi penelitian seluruh pasangan usia subur di wilayah Telukjambe tepatnya di Desa Curug Kecamatan Klari Kabupaten sebanyak 150 responden. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel 60 responden. Analis bivariate menggunakan uji Chi-square. Berdasarkan uji chi square dengan CI = 95% diperoleh p value .001 (P 0,05) yang berarti ada hubungan yang signifikan antara budaya patriarki dan pengambilan keputusan dalam ber KB pada pasangan usia produktif di Desa Curug Kecamatan Klari Kabupaten Karawang tahun 2023. Simpulan ada hubungan yang signifikan antara budaya patriarki dan pengambilan keputusan dalam ber KB pada pasangan usia produktif di Desa Curug Kecamatan Klari Kabupaten Karawang tahun 2023. Disaran dalam penelitian ini untuk Institusi pendidikan, untuk tempat penelitian, untuk responden dan untuk peneliti selanjutnya. Kata Kunci: Budaya Patriarki, KB, Usia Reproduksi